Circulating Tumor DNA as a Potential Marker to Detect Minimal Residual Disease and Predict Recurrence in Pancreatic Cancer - Jiang, Jiahong; Ye, Song; Xu, Yaping; Chang, Lianpeng; Hu, Xiaoge; Ru, Guoqing; Guo, Yang; Yi, Xin; Yang, Liu; Huang, Dongsheng (Frontiers in Oncology, 2020)
Pancreatic ductal adenocarcinoma (PDAC) is one of the leading causes of cancer death, partly due to the high recurrence rates for patients with PDAC. Current postoperative surveillance methods, including monitoring of clinical symptoms, tumor markers, and CT imaging, lack sensitivity and specificity for minimal residual disease (MRD). We investigated whether the detection of circulating tumor DNA (ctDNA) could identify MRD and predict relapse in postoperative patients with PDAC. In this study, we performed panel-captured sequencing to detect somatic mutations. Matched tissue samples were obtained to verify mutation. A total of 27 patients and 65 plasma samples were included. Among the somatic mutations, KRAS and TP53 were the most recurrent genes in both tissue and plasma samples. The detectable rate of ctDNA increased with the stage of PDAC. The maximal variant allele fraction (VAF) of ctDNA had a positive correlation with tumor largest diameter (p = 0.0101). Patients with ctDNA-positive status postoperatively had a markedly reduced disease-free survival (DFS) compared to those with ctDNA-negative status (HR, 5.20; p = 0.019). Positive vascular invasion significantly influenced disease-free survival (DFS) (p = 0.036), and positive postoperative ctDNA status was an independent prognostic factor for DFS (HR = 3.60; 95% CI, 1.15–11.28; p = 0.028). Postoperative ctDNA detection provides strong evidence of MRD and identifies patients with a high risk of relapse. ctDNA detection is a promising approach for personalized patient management during postoperative follow-up.